THE STOCKS OF ORGANIC CARBON IN THE BLOCK "LITTER – SOIL" OF POLISSIA REGION PINE ECOSYSTEMS - Raspopina, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of studies of the content and stocks of organic carbon in the block "litter – soil" of pine ecosystems in Zhytomyr and Chernihiv Polissia are presented. The forest ecosystems are important stabilizers of the carbon cycle as well as stocks of carbon. The components of the forest ecosystem are interconnected by the flows of energy and substances. Binding СО2 in the block of "plant-soil", followed by the transformation of carbon into insoluble humus compounds is of particular importance. In the research area sod - light-podzolic and sod-medium-podzolic soils on fluvioglacial sands are mostly spread. These soils belong to the category of old arable ones. Present here are also peat – marsh soils. It is shown that the process of humus accumulation is characterized by low intensity, which is caused by a complex of reasons, in particular, the sandy composition of sod-podzolic soils (particle content < 0,01 mm – 7,5 %).The thickness of the profile humus portion is 18 cm. The average content of humus is 0,97 %, and reserves – 28,3 t/ha in a 20-cm layer. Similar indicators of carbon are 0,56 % and 16,4 t/ha, respectively. Organic substance of sod-podzolic soils of pine habitats is resistant to mineralization and for a long time is removed from the cycle of substances of the pine ecosystem. The average carbon content in hydromorphic organogenic soils increases to 18,1 % and its stocks are 168,9 t/ha. The ability for mineralization peat soils is lower than that of sod-podzolic soils. So, they have a high carbon sequestration capacity. Pine litter reserves on the average are 30–33 t/ha, and carbon reserves on the average are – 12,6 t/ha, with its stable content – 40 %.The total carbon reserves in the block "litter – soil" of a typical pine ecosystem of Polissia are on average 29 t/ha, with the bulk of them being concentrated in the soil. Considering that highly productive pine forests are formed on the infertile soils of Polissia, their afforestation will not only stop the intensive degradation of soils of Ukraine, but also will increase the deposition of greenhouse gases, which will help to prevent further climate change at the regional level.
Keywords: sod-podzolic soil; litter; pinus sylvestris; humus; carbon; mineralization of organic substance